APLIKASI ANDROID PROGRAM KERJA HIMAKOM - Rama Bayu Nugraha; Dwi Sakethi; Ardiansyah Ardiansyah (Jurnal Pepadun, 2022)
The Student Association of the Department of Computer Science, University of Lampung (Himakom) has many short- and long-term work programs. Lack of supervision in implementing work programs can evoke that issues in the implementation of work programs indeed even cannot be carried out. Accountability reports conducted at colloquy was still in printed form, apart from being less efficient, printed reports also take longer to compile the report. The author develops a work program application for Student Association of the Department of Computer Science, Faculty of Mathematics and Science, University of Lampung (Himakom) to provide convenience for the academics to obtain information, supervise, give advice about Himakom and assisting Himakom in making accountability reports as well as making it easier for the academic community to view and read accountability reports. The author succeeded in manufacturing Application Work Program Himakom Based Android, proven by the suitability of work program data in the application with work program data carried out by Himakom and academicians majoring in computer science can easily access information about Himakom. In addition, the author also tested using the questionnaire method, and got a score with an average index of 85.85%.